Magnificent voyagers : the U.S. exploring expedition, 1838-1842 - Viola, Herman J.; Margolis, Carolyn (Smithsonian Institution Press, 1985)
Account of the activities, chronology, mapping and botanical and zoological collections of the United States Exploring Expedition of 1838-1842, which mapped 1500 miles of the Antarctic coast and proved that the continent exists. Published in connection with the exhibition 'Magnificent Voyagers' organized by the National Museum of Natural History and circulated by the Smithsonian Institution, Washington, D.C.